Green engineered biomolecule-capped silver and copper nanohybrids using Prosopis cineraria leaf extract: Enhanced antibacterial activity against microbial pathogens of public health relevance and cytotoxicity on human breast cancer cells (MCF-7). (April 2017) - Jinu, U.; Gomathi, M.; Saiqa, I.; Geetha, N.; Benelli, G.; Venkatachalam, P.
Abstract: This research focused on green engineering and characterization of silver (PcAgNPs) and copper nanoparticles (PcCuNPs) using Prosopis cineraria ( Pc ) leaf extract prepared by using microwave irradiation. We studied their enhanced antimicrobial activity on human pathogens as well as cytotoxicity on breast cancer cells (MCF-7). Biofabricated silver and copper nanoparticles exhibited UV–Visible absorbance peaks at 420 nm and 575 nm, confirming the bioreduction and stabilization of nanoparticles. Nanoparticles were characterized by FTIR, XRD, FESEM, and EDX analysis. FTIR results indicated the presence of alcohols, alkanes, aromatics, phenols, ethers, benzene, amines and amides that were possibly involved in the reduction and capping of silver and copper ions. XRD analysis was performed to confirm the crystalline nature of the silver and copper nanoparticles. FESEM analysis suggested that the nanoparticles were hexagonal or spherical in shape with size ranging from 20 to 44.49 nm and 18.9–32.09 nm for AgNPs and CuNPs, respectively. EDX analysis confirmed the presence of silver and copper elemental signals in the nanoparticles. The bioengineered silver and copper nanohybrids showed enhanced antimicrobial activity against Gram-positive and Gram-negative MDR human pathogens. MTT assay results indicated that CuNPs show potential cytotoxic effect followed by AgNPs against MCF-7 cancer cell line. IC50 were 65.27 μg/ml, 37.02 μg/ml and 197.3 μg/ml for PcAgNPs, PcCuNPs and P. cineraria leaf extracts, respectively, treated MCF-7 cells. The present investigation highlighted an effective protocol for microwave-assisted synthesis of biomolecule-loaded silver and copper nanoparticles with enhanced antibacterial and anticancer activity. Results strongly suggested that bioengineered AgNPs and CuNPs could be used as potential tools against microbial pathogens and cancer cells. Graphical abstract: Highlights: An efficient protocol for green engineered AgNPs and CuNPs using Prosopis cineraria leaf extract was established. Fabricated biomolecule-capped nanoparticles were characterized by using FT-IR, XRD, FESEM and EDX analysis. The synthesized nanoparticles showed enhanced antibacterial activity against microbial pathogens. Green engineered biomolecule-capped silver and copper nanoparticles exhibited efficient cytotoxicity against human breast cancer cell (MCF-7) line.